2018
DOI: 10.1103/physrevb.98.064509
|View full text |Cite
|
Sign up to set email alerts
|

Theory of superconductivity in hole-doped monolayer MoS2

Abstract: We theoretically investigate the Cooper-pair symmetry to be realized in hole-doped monolayer MoS2 by solving linearized BCS gap equations on the three-orbital attractive Hubbard-like model in the presence of the atomic spin-orbit coupling. In hole-doped monolayer MoS2, both spin-orbit coupling and the multi-orbital effects are more prominent than those of electron-doped system. Near the valence band edge, the Fermi surfaces are composed of three different types of hole pockets, namely, one mainly consisting of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The pairing of electrons with additional internal degrees of freedom resulting, e.g., from different orbitals or basis sites, can lead to qualitatively new pairing states. Such pairing states have for example been proposed for iron-based superconductors [2][3][4][5][6][7][8][9], Cu x Bi 2 Se 3 [10,11], cubic systems such as half-Heusler compounds [12][13][14][15][16][17][18][19][20][21], UPt 3 [22,23], transition-metal dichalcogenides [24,25], and twisted bilayer graphene [26][27][28]. It has been shown that in centrosymmetric multiband superconductors that break TRS, point and line nodes are generically "inflated," by interband pairing, into Fermi surfaces of Bogoliubov quasiparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The rich electronic properties of TMDs have stimulated several proposals for topological and unconventional superconductivity [16][17][18][19][20][21][22][23][24][25][26]. In [27,28] it was proposed that an Ising spin-orbit coupled monolayer TMD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Ising-type SOC locks the electron spin in the out-of-plane direction, the in-plane spin susceptibility is expected to be enhanced in contrast to the Rashba SOC systems. The layered transition-metal dichalcogenides (TMDCs), MX 2 (M = Mo, W and X = S, Se, and Te) are new platform for exotic superconductivity in context of noncentrosymmetric Ising-type spin-orbit physics [19][20][21][22][23][24][25]. The representative material of the TMDCs, MoS 2 , shows the electric-field-induced electron-doped superconductivity, whose in-plane upper critical field is about three times larger than the Pauli limit at 1.5 K due to the Isingtype SOC [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The representative material of the TMDCs, MoS 2 , shows the electric-field-induced electron-doped superconductivity, whose in-plane upper critical field is about three times larger than the Pauli limit at 1.5 K due to the Isingtype SOC [26,27]. The hole-doped TMDCs would be much interesting because of the multi-orbital features in the valence bands originating from the transition-metal d orbitals with relatively strong SOC [23,25]. Thin layer NbSe 2 and TaS 2 belonging to a family of TMDCs (the former can be viewed as heavily hole-doped MoS 2 ) also exhibit the large in-plane upper critical field.…”
Section: Introductionmentioning
confidence: 99%